EFEKTIFITAS PENGGUNAAN BAHASA PADA INSTRUKSI KESELAMATAN DI KONSTRUKSI TWIN TOWER UPN ”VETERAN” JAWA TIMUR - Gunawan, Rizal; Aljabar, Muhammad; Raffif, Jericho Waliudin; Wibowo, Mukti; Wardana, Agus Setiawan Kusuma; Sholihatin, Endang (Universitas Sultan Ageng Tirtayasa, 2024)
Occupational safety is paramount in construction, particularly in large-scale projects like the construction of the UPN